The future of food: domestication and commercialization of indigenous food crops in Africa over the third decade (2012–2021) - Leakey, R.R.B.; Tientcheu Avana, M.-L.; Awazi, N. P.; Assogbadjo, A. E.; Mabhaudhi, Tafadzwanashe; Hendre, P. S.; Degrande, A.; Hlahla, S.; Manda, L. (MDPI, 2022)
This paper follows the transition from ethnobotany to a deeper scientific understanding of the food and medicinal properties of African agroforestry tree products as inputs into the start of domestication activities. It progresses on to the integration of these indigenous trees as new crops within diversified farming systems for multiple social, economic and environmental benefits. From its advent in the 1990s, the domestication of indigenous food and non-food tree species has become a global programme with a strong African focus. This review of progress in the third decade is restricted to progress in Africa, where multi-disciplinary research on over 59 species has been reported in 759 research papers in 318 science publications by scientists from over 833 research teams in 70 countries around the world (532 in Africa). The review spans 23 research topics presenting the recent research literature for tree species of high priority across the continent, as well as that in each of the four main ecological regions: the humid zone of West and Central Africa; the Sahel and North Africa; the East African highlands and drylands; and the woody savannas of Southern Africa. The main areas of growth have been the nutritional/medicinal value of non-timber forest products; the evaluation of the state of natural resources and their importance to local people; and the characterization of useful traits. However, the testing of putative cultivars; the implementation of participatory principles; the protection of traditional knowledge and intellectual property rights; and the selection of elite trees and ideotypes remain under-researched. To the probable detriment of the upscaling and impact in tropical agriculture, there has been, at the international level, a move away from decentralized, community-based tree domestication towards a laboratory-based, centralized approach. However, the rapid uptake of research by university departments and national agricultural research centres in Africa indicates a recognition of the importance of the indigenous crops for both the livelihoods of rural communities and the revitalization and enhanced outputs from agriculture in Africa, especially in West Africa. Thus, on a continental scale, there has been an uptake of research with policy relevance for the integration of indigenous trees in agroecosystems and their importance for the attainment of the UN Sustainable Development Goals. To progress this in the fourth decade, there will need to be a dedicated Centre in Africa to test and develop cultivars of indigenous crops. Finally, this review underpins a holistic approach to mitigating climate change, as well as other big global issues such as hunger, poverty and loss of wildlife habitat by reaping the benefits, or ‘profits’, from investment in the five forms of Capital, described as ‘land maxing’. However, policy and decision makers are not yet recognizing the potential for holistic and transformational adoption of these new indigenous food crop opportunities for African agriculture. Is ‘political will’ the missing sixth capital for sustainable development?